Implementasi Technology Acceptance Model dalam Penggunaan E-Money Terhadap Minat Menggunakan E-Money Dengan Pengaruh Resiko Penggunaan Sebagai Variabel Mediasi Perspektif Ekonomi Syariah - Nurul Fadhila Hasanah; Miswardi Miswardi; Dila Anggraini; Habil Febrian; Anwar Sholihin (ITB AAS INDONESIA Surakarta, 2023)
This study was conducted to measure the effect of the direct test of the TAM variable (perceived benefits, perceived ease of use and perceived trust) and the effect of the indirect test of the TAM variable on the intention to use e-money which is mediated by the risk of use. This research is a quantitative study conducted through a survey using a questionnaire on brizzi card users in Bukittinggi and analyzed using SEM PLS (Partial Least Square) with the WarpPLS 6.0 program on 91 respondents with the criteria of having parked their vehicle 2x or more in the mandatory brizzi card parking lot in the city. Bukittinggi. Based on the results of the study with the direct effect test revealed that the perceived ease of use variable has the greatest influence on the intention to use with a value of 0.464 and a significance value of p